Investigations on dislocation density and strain of polyaniline withWO3nanocomposites. Issue 1 (1st March 2022) - Vijaykumar, B T; Bharati, B; Priyanka, K; Ramabai,; Manjunatha, B; Sannakki, Basavaraja
Abstract: Polyaniline is equipped by in-situ chemical oxidative polymerization method using ammonium persulphate as an oxidizing agent. The prepared Polyaniline is doped with the nano particles of WO3 at dissimilar weight percentage. The nano-compsites are characterized using XRD and SEM. The crystallite sizes are obtainvia Debye-Scherer relation from the XRD spectra for nano-composites of different weight percentages. The crystallite sizes of nano-particles decreased with increase in weight percentage of WO3 with the PANI. The dislocation density due to the defects in the crystals of nano-composites is obtained. The dislocation density increased as wt % of WO3 in PANI increased. Further, the strain produce at the grain boundary is obtained by FWHM of the XRD spectra. The strain of nano-composites at the grain boundary increased as dislocation density increased. Strain at the grain boundary is also increased as weight percent of WO3 increased in the nano-composites of PANI. Further, the surface morphology of the nano-composites of PANI/WO3 at different weight percentages were observed using SEM. The particles are appeared granular in shape and size. The agglomeration in the sizes of the nano-composites was observed as weight percent of WO3 with PANI increased.